Kesiapan Guru PAI dalam Menerapkan Kurikulum Merdeka Belajar pada SD Negeri di Kabupaten Aceh Tengah - Khakleri, Wien; Abdussyukur (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
This study explored the readiness of PAI teachers to implement the Independent Curriculum at SDN Aceh Tengah. It also explores existing difficulties and opportunities. This research focuses on the preparation, implementation, evaluation, and challenges teachers face. This research was conducted in 3 elementary schools. The sources of research data are principals, deputy heads of curriculum sections, and PAI teachers. The method used in this study is qualitative-descriptive. The data collection techniques used are interviews, observation, and documentation. The results of this study show PAI teachers' readiness to implement the independent curriculum. This is supported by ever-increasing understanding and support among teachers. Teachers' difficulties in implementing the Independent Curriculum are limited resources, time management, and labor shortages. The solution to this problem is through learning communities, collaboration, independent training, and an increased budget for mobilizing schools to be more accessible to implement and improve teachers' abilities.